2020
DOI: 10.1111/jocn.15517
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of professional quality of life through reducing fears of compassion and compassion fatigue: Application of the Compassionate Mind Model to Specialist Community Public Health Nurses (Health Visiting) training

Abstract: Aims and Objectives To identify whether a Compassionate Mind Model‐based curriculum reduces students’ perceived fears of compassion and improves their professional well‐being. Background Enabling compassion is mandatory within nurse education but evidencing it is challenging. Research suggests that application of the Compassionate Mind Model might reduce students’ fears of compassion and also decrease compassion fatigue. This study reports outcomes of a post‐registration curriculum based on that model for trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…56 In nursing, various projects with mindfulness and compassion training have been published e.g. 40,50,[57][58][59][60][61][62][63] Walker and Mann especially argue for mindfulness and contemplation related to compassion in nursing education. In the health care culture, they highlight how aspects of reflection and contemplation are needed to maintain balance and health in stressful clinical contexts.…”
Section: Clinical Application-compassion As a Capabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…56 In nursing, various projects with mindfulness and compassion training have been published e.g. 40,50,[57][58][59][60][61][62][63] Walker and Mann especially argue for mindfulness and contemplation related to compassion in nursing education. In the health care culture, they highlight how aspects of reflection and contemplation are needed to maintain balance and health in stressful clinical contexts.…”
Section: Clinical Application-compassion As a Capabilitymentioning
confidence: 99%
“…An intervention study 2021, on nursing students found that application of the compassionate mind model reduced their fear of compassion and decreased their risk of compassion fatigue. 40 Additionally, the incidence of burnout and compassion fatigue in nurses was shown in a meta-synthesis to have an opposite relationship to education. The higher the education, the less compassion fatigue, and the more compassion-satisfaction.…”
Section: Compassion Fatigue and Compassion Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMT has been found to increase HCP's abilities to support themselves (self-compassion), lessen their self-criticism, and help them tolerate distressing emotions ( Beaumont et al, 2016 ). McVicar et al (2021) and McEwan et al (2020) found that burnout scores decrease after CMT, whereas compassion satisfaction related to work and levels of well-being increase. A number of internet-based CMT interventions have shown promising results regarding increasing self-compassion and reducing depression, anxiety ( Kelman et al, 2018 ; Krieger et al, 2019 ), and stress ( Finlay-Jones et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although compassionate care is the cornerstone of the nursing profession and high quality health care, working in environments that are constantly dealing with the suffering and even death of patients may affect nurses’ compassionate behavior (McVicar et al, 2021). In some contexts, nurses may separate themselves from patients and try to deliver routine care rather than compassionate care that is active, committed, and empathetic (Blewitt et al, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%